2003
DOI: 10.1097/01.ju.0000081425.66782.c7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Vaginal Atresia at a Missionary Hospital in Bangladesh: Results and Followup of 20 Cases

Abstract: Good perioperative preparation and assistance, assurance of cyclical followup and a trained surgical team permitted successful treatment of a complex genital malformation at a missionary hospital with modest services. Sigmoid vaginoplasty in a developing country seems to be the best choice because of simple management and followup. Young women unable to procreate because of vaginal atresia seem to have an unexpected normal family and social acceptance in Bangladesh after complete vaginal replacement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…25 We previously reported our experience with young women treated in a developing country. 26,27 That experience emphasized how sigmoid vaginoplasty seems to be the best choice due to simple management and followup. However, we did not clearly evaluate the functional outcome at that time.…”
Section: Discussionmentioning
confidence: 99%
“…25 We previously reported our experience with young women treated in a developing country. 26,27 That experience emphasized how sigmoid vaginoplasty seems to be the best choice due to simple management and followup. However, we did not clearly evaluate the functional outcome at that time.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that in Bangladesh a man may abandon a woman with a condition such as MRKH. 25 It was found that in India women did not seek medical help until the time of marriage arrangements. The families were counseled to marry their daughters to widowers who had already completed their families or to men who were physically challenged and wanted to adopt children.…”
Section: Quality Of Life Outcomesmentioning
confidence: 99%
“…No major complication occurred in the patients who had undergone sigmoid vaginoplasty. Del Rossi et al [20] reported similar results. Hensle and Chang [21] used sigmoid colon in 20 patients, cecum in five patients, and ileum in eight patients.…”
Section: Discussionmentioning
confidence: 61%